Tavčarjevo župansko devetletje 1912-1921 - Perovšek, Jurij (Studia Historica Slovenica, 2017)
Under Tavčar's governance, Ljubljana retained the achieved level of municipal development, while Tavčar himself did not express initiatives in this respect. There was also the war which did not support the development rhythm. Perhaps it would have been different in peacetime. For the Austrian period and almost up until its end, Tavčar's unequivocal Austrian patriotism was particularly noticeable. During the war, he emphasized it even more, without a shred of doubt. This was, on the one hand, beneficial to him, his city and its inhabitants - for some it was even a life-saving solution - on the other hand, according to some of the Mayor's private statements and his Yugoslavian enthusiasm later on, his Austrian patriotism could have had a double significance. But Tavčar was definitely obedient to Austria, with an ear for Slovenians, almost to the end, and his obedience was not influenced by his more or less powerful Yugoslav sentiment. He could not have been blamed for anything from Austria's point of view, and later he felt good in the Kingdom of Serbs, Croats and Slovenians. Tavčar's great merit was that, in terms of supply, the urban population satisfactorily survived the war years. His greatest accomplishment as mayor was his leadership in war time, thanks to which Ljubljana, with some deviations, survived the war with a basic standard of living, and avoided potential blows from the Austrian authorities. When the influence of Austria was no more, Tavčar diligently and with pleasure incorporated into the new Yugoslav reality.
Keywords: Ljubljana; lokalna samouprava; politična zgodovina; Slovenija; Tavčar, Ivan; zgodovina; župani